"Salaries : Computation, taxation, planning : dictionary for employers and employees ,1993-94 / edited by Shiavux Mistry" - "Mistry, Shiavux (ed.)" (New Delhi, 1993)
This book deals with tax and taxation of salaries.
Keywords: Taxation India 1993